Hybrid Cache Design Under Varying Power Supply Stability - A Comparative Study - Wilbert, Nils; Wildermann, Stefan; Teich, Jürgen (MEMSYS '24: Proceedings of the International Symposium on Memory Systems, 2024)
co As emerging Non-Volatile Memory (NVM) technologies are ever maturing, the usage of such novel memory technologies in embedded systems is becoming increasingly viable. Especially when introduced at the cache level, these technologies can promise great advantages over conventional SRAM technology as they can serve read requests at lower energy and, in applications of intermittent computing, reduce the backup overhead during a power outage. Nevertheless, write accesses to NVMs consume more energy compared to writing to a conventional SRAM. As a remedy, hybrid caches, introducing both NVM and SRAM to the cache hierarchy, can realize trade-offs by minimizing the expected NVM write overhead while still exploiting the NVM read efficiency and non-volatility property. However, these hybrid designs open up a number of additional decisions in the design space, which are examined in this paper. Most notably, the choice of the degree of non-volatility introduced to the cache hierarchy in addition to the choice of a suitable cache replacement policy has not been analyzed and solved systematically yet. By employing simulation-based experiments, we evaluate embedded applications featuring various memory access patterns under both continuous and intermittent power supplies for different types of hybrid cache designs. Our results show how the combination of application and architecture characteristics, in addition to the expected power supply stability, leads to a vast range of hard-to-predict cache effects affecting both performance and energy efficiency. Both the potential and a necessity for automated design tools, including the exploration of hybrid memory hierarchies, therefore arise.